E-Government Sebagai Realisasi Sistem Jaringan Terdesentralisasi Di Indonesia: Implikasi Sosial Dan Politik - Chairun Nisa Zempi; Siti Maryam; Priyono Priyono (Universitas Persada Indonesia YAI, 2022)
The decentralized system is the concept of granting authority by the central government tolocal governments to determine the policy direction of each region. E-government is present asthe realization of a social and political system that is decentralized and mediated by informationand communication technology. E-government is the use of technology by the government toprovide effective and efficient information and services to the public. The community can enjoyvarious programs, such as e-monitoring, e-education, e-office, e-permit, e-health, and mediacenter. In Indonesia, the development of e-government still needs to be improved. Severalproblems arise, such as lack of government socialization, limited human resources,infrastructure, which is still incomplete, access constraints are still challenging for some regions,and inadequate e-government services. Therefore, a joint contribution is needed between thegovernment, the private sector, the media, and the community to realize an e-government systemas a step towards open government and good governance.